Dual-function perovskite light-emitting/sensing devices for optical interactive display - Songman Ju; Yangbin Zhu; Hailong Hu; Yang Liu; Zhongwei Xu; Jinping Zheng; Chaomin Mao; Yongshen Yu; Kaiyu Yang; Lihua Lin; Tailiang Guo; Fushan Li (Light: Science & Applications, 2022)
Schematic diagrams of SD-PQLED based on light interaction layer and light-emitting layer and proof-of-concept diagram of the light interactive display by a four-pixel SD-PQLEDs.